High resolution study of the 3v1 band of SO2; Journal of Molecular Spectroscopy; Vol. 255, iss. 2 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Horneman V.-M.; Alanko S.; Gromova O. V. Olga Vasilievna (2009, 2009)
Title screen